Kajian parameter gender dalam substansi peraturan perundang-undangan di Indonesia - Kadek Wiwik Indrayanti (Jurnal Cakrawala Hukum, 2021)
This article examines the objectives, principles, and integration of gender equality indicators in the formulation of laws. The method used is normative legal research because it examines some of the substance of laws that are gender biased. The results show that the role of the government in realizing gender equality in Indonesia today has been carried out through laws and regulations, policies and programs but still has to be fought for because in reality there is still a gap between the two sexes, which has an impact on gender discrimination. There are several laws whose substance shows discrimination against women, such as the Marriage Law. Therefore, the concept of gender equality should be understood as a "goal", so that both sexes as citizens can obtain their rights. There are three principles that must receive attention, namely basic equality, non-discrimination and the obligation of the State which is the opening door to improve conditions of gender inequality in society. These two principles should be accommodated in the legislation. Furthermore, the 4 gender indicators namely access, participation, control and opportunity should be integrated in an integrated manner starting from the manufacture of a legal product, then translated into policies and programs.How to cite item: Indrayanti, K. (2021). Kajian parameter gender dalam substansi peraturan perundang-undangan di Indonesia. Jurnal Cakrawala Hukum, 12(2), 195-204. doi:https://doi.org/10.26905/idjch.v12i2.6223